PENGARUH INFLASI,TINGKAT SUKU BUNGA DAN NILAI TUKAR RUPIAH/US DOLLAR TERHADAP RETURN SAHAM PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sri Suyati (FEB UNTAG Semarang, 2015)
Stocks of property are sector having high sensitivity to the chage of macro economic condition and having different stock return volatility. The aim of this research are to analyze the influence of economic macro indicator such as inflation, rate of interest and exchange rate of Rupiah / US Dollar. This research used analyzing statistic method. Independent variables are inflation, rate of interest and exchange rate of Rupiah /US Dollar Dependent variables are stock return of property. Technique sample used sensus method with listed criteria in Indonesian Stock Exchange which have a complete financial statement. Sample of research are consist of 25 property companies. Data technique analysis used in this research is double linier regression anylysis. The result of this research indicates that by parsial analysis with alpha (a) 0,05 find that inflation does have a significant effect to stock return of property but rate of interest. does have a significant effect to stock return of property, and exchange rate of Rupiah / US Dollar does have a significant effect to stock return of property.Keywords : inflation, interest rate, exchange rate, stock return